Effect of sugar mill effluent on changes of growth and amino acid and protein contents of maize (Zea mays L.) plants - M. Vijayaragavan3, D. Ezhilvannan1*, P.S. Sharavanan2 and (Journal of Ecobiotechnology, 2011)
The effect of sugar mill effluent on plant growth and biochemical constituents of Maize (Zea mays L.) was studied in a pot culture experiment. The experiment was conducted at Botanical Garden, Department of Botany, Annamalai University, Tamil Nadu. In the pot culture experiment, maize plants were grown up to 30th days, in the soil irrigated with different concentrations of sugar mill effluent (viz, 0, 20%, 40%, 60%, 80% and 100% v/v). The inner surfaces of pots were lined with a polythene sheet. Each pot containing 3kg of air dried soil. Six seeds were sown in each pot. All pots were irrigated (500 ml) with respective concentration of test solutions daily. Plants were thinned to a maximum of three per pots, after a week of germination. The higher sugar mill effluent concentrations (above 40%) were found to affect plant growth and decreased amino acids and protein contents, but diluted effluent (up to 40% ) favoured the plant growth and biochemical contents.